Monitoring and Evaluation as Key Factor in Performance of Health Institutions, A Case Study of Kigali Health Institute, Kigali Rwanda. - Jean, Pierrekwizera (Kabale University, 2020)
Within this study the researcher reports the findings on the investigation conducted on the contribution of monitoring and evaluation towards the performance in Health Institutions a case study of Kigali Health Institute, Kigali Rwanda. The sample of the study was composed by male and female of lecturers and students from Kigali Health Institute. The problem of this study was that monitoring and evaluation tools still face many challenges and have not offer enough and suitable information about performance in health institutions. Aim of the study was to investigate the contribution of monitoring and evaluation to the performance of health institutions in Rwanda. The data were collected by using a questionnaire. The study found that 79% of respondents says that monitoring and evaluation system is quality assurance 13% is assessment and research done on the performance and 8%says that monitoring and evaluation system used by KHI is evaluation of course design.85% of respondents says that the system generate information from student’s lecture evaluation form. 15%of respondents says that information is from the field where students who graduates from KHI works.94% of respondents from lecturers and staff and 89% of respondents from students say that monitoring and evaluation system has contributed to the performance of KHI. The following factors positively aspects on the monitoring and evaluation system has enhanced its performance: student’s failure and repeaters are very minimal, curriculum review and student –teacher assessment. After analyzing and presentation of the data the researcher discovers that results found are similar. According to what other authors said Monitoring and evaluation are complementary. The researcher recommended a need to enlarge the work not only Lecturers and students but also all Rwandan categories. The study recommended KHI as well as MINEDUC that they should have serious measures to introduce national policy in monitoring and evaluation system and different stakeholders should work hand in hand with KHI and other highlighted contributors so that the performance is taken as a priority among other program at KHI.